Chemoprophylaxis after oncological resections - Sheldon, Yarrow; Warner, Shelley; Johns, Michael; Gbadebo, Bayo; Caplan, Richard; Jurkovitz, Claudine; Petrelli, Nicholas; Tiesi, Gregory (Open Science Journal, 2023)
Background National societies recommend extended-duration VTE chemoprophylaxis for up to 4 weeks following major oncologic resections with the literature demonstrating an incidence of approximately 2% for symptomatic VTE. Despite this, patients are not routinely discharged on VTE chemoprophylaxis at our institution. Methods A retrospective chart review was performed for major abdominal oncologic resections, including esophagectomy, at an academic community cancer center between 2016 and 2021. The primary outcome was the incidence of clinically evident VTE events (defined as lower extremity deep vein thrombosis (LE DVT) or pulmonary embolism (PE)) within 30 days of discharge and diagnosed on re-presentation. Exclusion criteria included in-hospital mortality, in-hospital VTE, or discharge on anti-coagulation. Comparisons were performed using Fisher’s Exact and Mann-Whitney test. Results After exclusion criteria were applied, 458 patients were identified. A total of 6 (1.3%) patients developed symptomatic VTEs, 5 (1.1%) PEs and 3 (0.7%) DVTs. No procedural interventions were required. On average, patients re-presented 14.3 (±8.4) days after discharge. There were no mortalities within 30 days of discharge. Intraoperatively, estimated blood loss in VTE group was decreased (150 vs 88 mL, p=0.01), while length of inpatient hospitalization (6.5 vs 10 days, p=0.05) was increased. Type of operation demonstrated an increased proportion of esophagectomy (9.6% vs 16.7%, p=0.57), palliative bypass (8.1% vs 33.3%, p=0.08) and small bowel resection (7.9% vs 33.3%, p=0.08) in the VTE group. Conclusion The percentage of symptomatic VTEs in our patients was not higher then reported averages despite no patient receiving chemoprophylaxis. Questions remain as to which subset of patients would benefit from chemoprophylaxis after major abdominal oncologic resection. Further investigation into long term effects of asymptomatic DVT should be undertaken.